Enforcement on real estate that is not registered because the records have been destroyed or damaged - Stojana, (Glasnik Advokatske komore Vojvodine, 2026)
In both observed entities of Bosnia and Herzegovina - Republika Srpska and Federation of Bosnia and Herzegovina, there are areas where the existing records of immobility have been destroyed or damaged, and it is reported that the procedure for its restoration will be carried out. Since the process of establishing real estate records is lengthy, the legislators foresee special procedural rules when such real estate is proposed as the subject of enforcement. In this way, the legislators are trying to compensate the enforcement creditors for the still present irregular management of public registers, or their absence in certain areas, and to enable them to enforce on such immovable properties as well. This, especially in a situation where the enforcement creditor does not have another object of enforcement that he could propose.The goal of the research is a normative-dogmatic analysis of the domestic legislative model of execution on immovable property that is not registered in the public register, because it has been destroyed or damaged. From the analysis of the domestic and comparative procedural doctrine and available current domestic court practice, it emerges that the special rules of procedure that are applied in this situation in both entities of Bosnia and Herzegovina do not correspond to the interest of the enforcement seeker for an efficient settlement on such immovable properties. As a result of the observed weakened general principle of judicial management of the procedure, there is also a conclusion about the excessive burden on the enforcement creditor, and about the rare judicial implementation of the confiscation inventory of such immovable property.
Keywords: enforcement procedure, immovable propertiy, registration of right on immovable property, cadastre, land register